2018
DOI: 10.1186/s11671-018-2678-z
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Fullerene Anchored Reduced Graphene Oxide Hybrids and Their Synergistic Reinforcement on the Flame Retardancy of Epoxy Resin

Abstract: A C60-PEI-rGO hybrid was prepared by incorporating the fullerene (C60) on the surface of PEI-modified reduced graphene oxide (rGO) and then used to modify the epoxy (EP) resin. Subsequently, the structure of GO and C60-PEI-rGO hybrid were well characterized, showing that the C60 was homogenously anchored on the surface of PEI-rGO. The flame retardancy, mechanical properties, and thermal stability of as-prepared C60-PEI-rGO/EP nanocomposites were systematically investigated. Results show that the C60-PEI-rGO hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…In addition, a new band at 1460 cm −1 (light blue block) appears in PEI-rGO which is assigned to the C–N stretching vibration. 40 These observations fully indicate the successful grafting of PEI molecules onto the GO surface, confirmed by the changes in ζ from −42.28 mV of GO to 32.35 mV of PEI-rGO (Fig. 1b).…”
Section: Resultssupporting
confidence: 69%
“…In addition, a new band at 1460 cm −1 (light blue block) appears in PEI-rGO which is assigned to the C–N stretching vibration. 40 These observations fully indicate the successful grafting of PEI molecules onto the GO surface, confirmed by the changes in ζ from −42.28 mV of GO to 32.35 mV of PEI-rGO (Fig. 1b).…”
Section: Resultssupporting
confidence: 69%
“…[152] Alternative to this, recently, nanofillers have also been employed for stimulating the chemisorption instead of coupling reactions that avoid the interference of agglomeration. [153] However, the science of nanofillers is not new and similar to spacers applied since the early stages of research in nanographene. The principles of conventional donor-acceptor chemistry could be beneficial for the recently emerging photoinduced electron transfer for the synthesis of graphene-fullerene hybrid.…”
Section: Fullerene Functionalization With Graphenementioning
confidence: 99%
“…The corresponding peaks of the stretching and bending vibration of C-H bond appeared at 2800-3000 cm −1 and 1300-1500 cm −1 , respectively [40][41][42][43], as our findings also illustrated these absorption ranges as small peaks (Figures 4(b) and 4(c)). Moreover, previous findings reported that the absorption peak range of 1500-1650 cm −1 and 3000-3400 cm −1 were ascribed to N-H 7 Journal of Nanomaterials bending and stretching vibration region related to the amine groups of PEI molecules [44][45][46], which are illustrated in Figure 4(c) as a broad peak in the region of 3000 to 3500 cm −1 that seems to be overlapped with the peaks of O-H stretching vibrations.…”
Section: Resultsmentioning
confidence: 81%